Social and Environmental Risks Integration into Underwriting of Non-Life Insurance: A Review of Sustainable Finance in Indonesia - Maria Agnes; Raldi Hendro Koestoer; Ahyahudin Sodri (Jurnal Ilmu Lingkungan)
Regulation of the Financial Services Authority of Indonesia (POJK) Number 51/POJK.03/2017 concerning the Implementation of Sustainable Finance for Financial Services Institutions, Issuers, and Public Companies was officially enacted for the insurance sector as of 1 January 2020 and requires the insurance sector, including the general insurance sector, to carry out the implementation of sustainable finance into its business activities. This study intends to review the extent of the implementation that has been carried out, particularly in relation to the social and environmental risk management principles. Using a literature review, data specifically related to the underwriting process were gathered and analyzed. Results of this study suggested that even though 86% of 44 respondents from the previous research had already confirmed if principles of social and environmental risk management had been implemented at that time, vast majority of the non-life insurers in Indonesia had not yet executed the said integration into the underwriting process. The sustainable finance implemented by Indonesia’s non-life insurance sector is still significantly focused on short-term financial performance rather than the long-term one.